2016
DOI: 10.1038/srep20188
|View full text |Cite
|
Sign up to set email alerts
|

Subgroup J avian leukosis virus infection of chicken dendritic cells induces apoptosis via the aberrant expression of microRNAs

Abstract: Subgroup J avian leukosis virus (ALV-J) is an oncogenic retrovirus that causes immunosuppression and enhances susceptibility to secondary infection. The innate immune system is the first line of defense in preventing bacterial and viral infections, and dendritic cells (DCs) play important roles in innate immunity. Because bone marrow is an organ that is susceptible to ALV-J, the virus may influence the generation of bone marrow-derived DCs. In this study, DCs cultured in vitro were used to investigate the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…Accumulating evidences demonstrated that lncRNA growth arrest-specific 5 (GAS5) acted as a powerful regulator of various biological activities, including tumor metastasis [29], vascular remodeling [30], autoimmune and inflammatory diseases [31]. Recently, GAS5 has been reported to involve in autophagy in NSCLC cells [32], and negatively correlated with mTOR [33,34], which is a crucial regulator of autophagy [35]. Although GAS5 has been suggested to mediate autophagy program, the underlying mechanism still remains to be further confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidences demonstrated that lncRNA growth arrest-specific 5 (GAS5) acted as a powerful regulator of various biological activities, including tumor metastasis [29], vascular remodeling [30], autoimmune and inflammatory diseases [31]. Recently, GAS5 has been reported to involve in autophagy in NSCLC cells [32], and negatively correlated with mTOR [33,34], which is a crucial regulator of autophagy [35]. Although GAS5 has been suggested to mediate autophagy program, the underlying mechanism still remains to be further confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…From 2002 to 2010, ALV-J infection became a common infectious disease in China’s poultry industry [21]. Because of recent worldwide eradication efforts, ALV-J infection now rarely occurs in white-feather broilers, but has gradually returned to local chicken farms in China [22].…”
Section: Discussionmentioning
confidence: 99%
“…An ex vivo study demonstrated that ALV-J could infect bone marrow-derived DCs (BM-DCs) during the early stages of differentiation and trigger apoptosis (44). Further studies showed that ALV-J inhibits the differentiation and maturation of BM-DCs and alters cytokine expression, causing aberrant antigen presentation and an altered immune response (19).…”
Section: Immunity Against Alvmentioning
confidence: 99%
“…Chicken macrophages and DCs can be directly infected by ALV and induce innate immunity (40, 44). However, we still have no clear knowledge of the regulation of the global innate immune response to ALV infection and ALV evasion of the host innate immune response.…”
Section: Immunity Against Alvmentioning
confidence: 99%